2009
DOI: 10.1021/cg801347d
|View full text |Cite
|
Sign up to set email alerts
|

Wöhler and Liebig Revisited: 176 Years of Polymorphism in Benzamide - and the Story Still Continues!

Abstract: In 1832, Friedrich Wo ¨hler and Justus von Liebig described the existence of polymorphism in molecular crystals for the first time in the case of benzamide. 175 years later, the crystal structure of this historical polymorph could be finally solved. Surprising similarities regarding the packing motifs between all three known forms can be found. According to Ostwald's rule, high supersaturations are needed to crystallize the most unstable Form II from solution. Herein we present a way in which all three known f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 37 publications
(67 reference statements)
3
43
0
Order By: Relevance
“…70 Abraham and Medforth 18 studied the conformational equilibria of piperidine and some of its simple derivatives, including 1, with a bulky cobalt(III)-porphyrin shift reagent that binds specifically to the amine nitrogen atom. The spin-spin coupling constants in the 1 H NMR spectra of the resulting complexes revealed that the 75 equatorial position of the OH group in 1 was, as expected, favoured over the axial position, whereas the amine proton necessarily takes the axial position at nitrogen in both conformers, to allow the central atom of the shift reagent to coordinate at the equatorial position. This conformational equilibrium of 1 has also been analysed with the J-value method, 19,20 with similar conclusions; the equatorial conformer with respect to the OH group is some 0.8 kcal/mol more stable than the axial (perhaps surprisingly, this preference is reversed for the corresponding piperidinium cation).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…70 Abraham and Medforth 18 studied the conformational equilibria of piperidine and some of its simple derivatives, including 1, with a bulky cobalt(III)-porphyrin shift reagent that binds specifically to the amine nitrogen atom. The spin-spin coupling constants in the 1 H NMR spectra of the resulting complexes revealed that the 75 equatorial position of the OH group in 1 was, as expected, favoured over the axial position, whereas the amine proton necessarily takes the axial position at nitrogen in both conformers, to allow the central atom of the shift reagent to coordinate at the equatorial position. This conformational equilibrium of 1 has also been analysed with the J-value method, 19,20 with similar conclusions; the equatorial conformer with respect to the OH group is some 0.8 kcal/mol more stable than the axial (perhaps surprisingly, this preference is reversed for the corresponding piperidinium cation).…”
Section: Introductionsupporting
confidence: 66%
“…The ring shows the typical chair form and the OH substituent is, as expected,70 equatorially oriented (this is also true for all other structures presented here except 4, see below). More surprising perhaps is the axial orientation of the N-bonded hydrogen; it seems that packing effects, presumably associated with the hydrogen bond pattern, override the slight preference for the equatorial75 orientation observed in solution. One might speculate that, similarly to the behaviour of the shift reagent mentioned above, 18 the donor molecule acts as a bulky group and thus preferentially occupies the equatorial site at the acceptor nitrogen.…”
mentioning
confidence: 99%
“…10 In the year 2005 the structure of a highly metastable form II could be solved from synchrotron powder diffraction data collected with a 17:83 mixture with form I by David et al. 13 In all experiments concomitant crystallization 14 of form I and III, or with higher supersaturation, of form I, II, and III occurred. 12 Form I can be crystallized from aqueous solutions as a pure phase by cooling slowly.…”
Section: Introductionmentioning
confidence: 99%
“…15 In that line, Chaudhari et al followed the formation of hydrogen bonded dimers of benzamide and related compounds in deuterated chloroform solution by NMR using diffusion ordered spectroscopy (DOSY) and other techniques and established association constants for the complex formation in solution suggesting that polymorphs of benzamide might be selected in a similar way by the appro-priate choice of solvent. 12,13 For this reason, the polymorph selection is expected to be little in-fluenced by the choice of solvent. The crystal structures only differ by the packing of these ribbons via comparatively week π-π-stackings.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Furthermore, there were, as with 2-chlorobenzamide, similarities in the packing motifs of the polymorphs. 6 Relatively recent predictive studies on benzamide identified the three polymorphs in a complex energy landscape. The authors 7 suggest that the metastable polymorph described by 3 Wöhler and Liebig 175 years ago could have been solved earlier, had CSP methods been available.…”
Section: Introductionmentioning
confidence: 99%